From Twin Towers to Fawlty Towers: The story of the Doha Round - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2008)
The Doha Round has yet again collapsed. The July 2008 attempt to negotiate a broad headline deal between the main member countries of the WTO failed. The Round is already way beyond bedtime and members now need to ask themselves: Is it at all meaningful to continue the Round - or should it be put at sleep permanently? This paper aims at examining the structural problems of the Doha Round and, by extension, the WTO and its current institutional setup. It offers a broad stock take of the current climate of trade negotiations and offers explanations to the failing Doha efforts to liberalise trade.
Keywords: 330